Emplacing Climate Change: Civic Action at the Margins - Castro-Sotomayor, José (Frontiers in Communication, 2019)
In this paper, I use my work with the Gran Familia Awá Binacional (GFAB), an indigenous transboundary organization located at the border between Ecuador and Colombia, to redirect attention to ways organizations at-the-margins perform civic action. I understand at-the-margin organizations as those that (1) are not located in urban spaces; (2) have limited access to technology; and, (3) use non-dominant languages as a central element of their collective identity and struggle. Due to the increasing urban bio- and geo-graphy of the world, it seems that the literature on civic action has taken an expected shift in focus to reserve the attribution of civic action to movements taking place in cities; further, the influence attributed to technology in fostering collective action appears to divert attention away from organizations or movements whose practices are not dependent on, started from, and enhanced by technological innovations. I use Lichterman and Eliasoph’s (2014) definition of civic action — a kind of coordination that entails actions and relationships rather than beliefs, values, or a predefined social sector — to argue that as a communication practice and historicist inquiry (Briziarelli & Martínez Guillem, 2016), translation is an epistemological device used by at-the-margin organizations to create spaces for civic action via the constant process of disturbing the language and rethinking the meaning embedded in hegemonic global environmental discourses such as climate change. I illustrate how members of the GFAB emplace the meaning of climate change, which I argue, is a rhetorical move that suggests a phenomenological place-based conceptualization of climate change that could function as both, a decolonial strategy and a pragmatic environmental communication that constitutes spaces for civic action to thrive.